2020
DOI: 10.1007/s40820-020-00548-5
|View full text |Cite
|
Sign up to set email alerts
|

3D Lamellar-Structured Graphene Aerogels for Thermal Interface Composites with High Through-Plane Thermal Conductivity and Fracture Toughness

Abstract: Highlights Lamellar-structured graphene aerogels with vertically aligned and closely stacked high-quality graphene lamellae are fabricated. The superior thermally conductive capacity of the aerogel endows epoxy with a high through-plane thermal conductivity of 20.0 W m −1 K −1 at 2.30 vol% of graphene content. The nacre-like structure endows the epoxy composite with enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(106 citation statements)
references
References 67 publications
(89 reference statements)
4
101
0
1
Order By: Relevance
“…However, as the amount of CCA@rGO increases further, the internal rGO of CCA@rGO tends to agglomerate, which reduces the density of the thermal conductivity network inside the CCA@rGO/PDMS electromagnetic shielding composites [ 56 , 57 ]. However, with the further increase in the loading of CCA@rGO, the rGO inside CCA@rGO tends to agglomerate, which decreases the density of the thermal conductivity network inside the CCA@rGO/PDMS EMI shielding composites, thus adversely affecting the λ and α of the CCA/PDMS EMI shielding composites [ 58 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…However, as the amount of CCA@rGO increases further, the internal rGO of CCA@rGO tends to agglomerate, which reduces the density of the thermal conductivity network inside the CCA@rGO/PDMS electromagnetic shielding composites [ 56 , 57 ]. However, with the further increase in the loading of CCA@rGO, the rGO inside CCA@rGO tends to agglomerate, which decreases the density of the thermal conductivity network inside the CCA@rGO/PDMS EMI shielding composites, thus adversely affecting the λ and α of the CCA/PDMS EMI shielding composites [ 58 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…To increase the thermal conductivity of the macroscale assembled carbons, Xin et al [ 107 ] fabricated a densely stacked porous graphene film with use of a mechanical compression method, showing an excellent thermal conductivity over 1400 W m −1 K −1 due to the substantially reduced contact thermal resistance. Furthermore, Liu et al [ 108 ] fabricated a lamellar structured 3D graphene aerogels which composed of vertically aligned and densely stacked graphene nanosheets and demonstrated an excellent out‐of‐plane thermal conductivity. When compositing with polyamic acid salt followed by a bidirectional freeze‐drying method, a superior out‐of‐plane thermal conductivity was afforded with a very high value over 20 W m −1 K −1 .…”
Section: Thermal Conductive Additivesmentioning
confidence: 99%
“…Recent developments in electronic technology have enabled the integration and miniaturization of microelectronic devices, allowing more transistors to be integrated into a single chip for better performance. [1][2][3][4][5] The increase of miniaturization, high-degree integration, and multifunctionalities of those modern devices release more heat, which will greatly affect their performance and reliability, and bring huge challenges to the development of microelectronics. [6][7][8][9] Polymer-based nanocomposites with enhanced thermal conductivity have been demonstrated as effective thermal management materials to solve those overheating issue.…”
Section: Introductionmentioning
confidence: 99%
“…In consequence, the development of polymer nanocomposites with desired mechanical performance, high thermal conductivity, and electrical insulation has attracted much attention. [4,[10][11][12][13][14][15][16][17][18] The traditional thermally conductive polymer-based nanocomposites are produced by simply adding a kind of inorganic filler, leading to poor thermal conductivity, high cost, and reduced mechanical properties, thus greatly hindering its practical application in industry. [19] Recent studies revealed that the effective method to meet this challenge of improving the thermal conductivity of polymer-based composites is to establish a three-dimensional (3D) interconnection thermal network in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%